Eating patterns and nutrient intake for older people: Analysis with different methodological approaches - Ferreira-Nunes, Patrícia Moraes; Papini, Silvia Justina [UNESP]; Corrente, José Eduardo [UNESP] (FapUNIFESP (SciELO), 2018)
This study aims to analyse the eating patterns and nutrient intake in different eating patterns of elderly persons. This is a cross-sectional study with elderly people from Botucatu, São Paulo state, Brazil. The mean daily nutrient intake of individuals with high adherence to the eating patterns identified by factor analysis was analysed, comparing the intake by analysis of variance. Individuals with high adherence to the Healthy eating pattern had the highest mean intake of retinol, vitamin A and vitamin E. Individuals with high adherence to the eating pattern Snacks and weekend meal presented lower means of vitamin B12, vitamin C, phosphorus, and retinol intake and the highest means of iron, manganese and magnesium intake. Individuals with high adherence to Fruits had the lowest mean fibre intake. Individuals with high adherence to Light and whole foods had the highest means of vitamin C intake. Individuals with high adherence to Soft diet showed lower protein intake and increased added sugar intake. Individuals with high adherence to the Traditional eating pattern presented high means of nutrient intake. In general, a better characterization of the eating behaviour of elderly people who adhere to each of these eating patterns was possible.
Keywords: Eating patterns; Elderly; Food; Macronutrients; Micronutrients